Observatórios locais de políticas públicas no Brasil: seu papel na produção, disseminação e transparência das informações - Beuttenmuller, Gustavo (2007)
The main objective of this work is to study local policy observatories and their contribution to democracy regarding transparency and production of information. Due to the fact that policy observatories haven’t been extensively studied this work has an exploratory feature with the purpose of helping comprehending the origins of this kind of institution and the description and analysis of their main characteristics, by emphasizing their main objective of producing information regarding public policies at local government levels. The empiric analysis intended to enhance the comprehension of this institutional phenomenon by presenting two case studies of local policy observatories in Brazil: the Observatório de Cidadania in São Paulo and the Observatório das Metrópoles in Rio de Janeiro. In both case studies the aim was to reveal their main characteristics, by analyzing their objectives and carried out activities, those that were related to the production, propagation and “translation” of information (in order to make them accessible to the ordinary citizen), and also its usage in the monitoring of public policies. The information on the case studies came from the analyzes of: documents (publications and institutional reports) the observatories, websites, interviews and observations made at the observatories main office. The obtained results correlate the origins of these institutions in Brazil to the historical context of the re-democratization and to its social actors and themes brought up from that context. The attempt was to present the complexity of this institutional arrangement which, aiming at the production of qualified information associated with modern technology and communication, has also become an area for inter-social relations, once they are developed between characters from Universities, NGOs and social movements. Finally it also aimed at demonstrating the contribution of these institutions to the strengthening of excluded sectors of the society in order to enable their participation, social control, and for the development of an active citizenship.